Tourism Village Development through Media Extension and Marketing Promotion Communication - Dahana, Kres; Sulaiman, Adhi Iman; Sari, Lilik Kartika (Technium Social Sciences Journal, 2023)
Tourism villages are community-based and sustainable development, aiming to improve people’s welfare, environmental and cultural sustainability, and improve the quality of human resources. Efforts to increase tourist visits to tourist villages by conducting marketing promotions. The key to marketing promotion is proper communication with potential tourists using the right media. The purpose of this study was to analyze the application of integrated marketing communication for tourism village marketing promotions. The theory used is Robyn Blakeman’s integrated marketing communication theory. This study uses a mixed method with data collection through questionnaires, observation, in-depth interviews, and Focus Group Discussion (FGD). Data were analyzed using quantitative descriptive analysis and qualitative analysis. The research informants came from elements of the village government, tourism village managers, women’s groups, and business groups. The research location was in Cikakak Village, Wangon District, Banyumas Regency, Central Java Province, Indonesia. The research results show: (1) Media have been implemented, with different application intensities. (2) Promotional media that are often or always used include public relations, social media, the internet, telephone and SMS, alternative media, and personal selling. (3) Promotional media that are rarely used include advertising, billboards, direct marketing, and sales promotion media that are rarely used include advertising, billboards, direct marketing, and sales promotion.